2023
DOI: 10.3390/nano13152220
|View full text |Cite
|
Sign up to set email alerts
|

Conductometric Gas Sensor Based on MoO3 Nanoribbon Modified with rGO Nanosheets for Ethylenediamine Detection at Room Temperature

Hongda Liu,
Jiongjiang Liu,
Qi Liu
et al.

Abstract: An ethylenediamine (EDA) gas sensor based on a composite of MoO3 nanoribbon and reduced graphene oxide (rGO) was fabricated in this work. MoO3 nanoribbon/rGO composites were synthesized using a hydrothermal process. The crystal structure, morphology, and elemental composition of MoO3/rGO were analyzed via XRD, FT-IR, Raman, TEM, SEM, XPS, and EPR characterization. The response value of MoO3/rGO to 100 ppm ethylenediamine was 843.7 at room temperature, 1.9 times higher than that of MoO3 nanoribbons. The MoO3/rG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The introduction of MoS 2 facilitates easier electron capture and reduces hindrance. The lowest slope observed for In 2 O 3 @MoS 2 -2 aligns with its superior gas sensitivity performance, demonstrating a higher response to H 2 S. Figure b displays the EIS plots of the five samples, used to illustrate the materials’ electron transfer capabilities . It can be observed that pure MoS 2 exhibits the smallest charge transfer resistance, indicating that the introduction of the two-dimensional material MoS 2 enhances resistance transfer capabilities.…”
Section: Experiments and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The introduction of MoS 2 facilitates easier electron capture and reduces hindrance. The lowest slope observed for In 2 O 3 @MoS 2 -2 aligns with its superior gas sensitivity performance, demonstrating a higher response to H 2 S. Figure b displays the EIS plots of the five samples, used to illustrate the materials’ electron transfer capabilities . It can be observed that pure MoS 2 exhibits the smallest charge transfer resistance, indicating that the introduction of the two-dimensional material MoS 2 enhances resistance transfer capabilities.…”
Section: Experiments and Discussionmentioning
confidence: 71%
“…The lowest slope observed for In 2 O 3 @MoS 2 -2 aligns with its superior gas sensitivity performance, demonstrating a higher response to H 2 S. Figure 7b displays the EIS plots of the five samples, used to illustrate the materials' electron transfer capabilities. 30 It can be observed that pure MoS 2 exhibits the smallest charge transfer resistance, indicating that the introduction of the twodimensional material MoS 2 enhances resistance transfer capabilities. In the composite material, In 2 O 3 @MoS 2 -2 shows the lowest charge transfer resistance, leading to better gas sensitivity and selectivity and a faster response−recovery time.…”
Section: ■ Experimental and Methodsmentioning
confidence: 95%